Critical Review on Low‐Temperature Li‐Ion/Metal Batteries. Issue 15 (26th February 2022) - Zhang, Nan; Deng, Tao; Zhang, Shuoqing; Wang, Changhong; Chen, Lixin; Wang, Chunsheng; Fan, Xiulin
Abstract: With the highest energy density ever among all sorts of commercialized rechargeable batteries, Li‐ion batteries (LIBs) have stimulated an upsurge utilization in 3C devices, electric vehicles, and stationary energy‐storage systems. However, a high performance of commercial LIBs based on ethylene carbonate electrolytes and graphite anodes can only be achieved at above −20 °C, which restricts their applications in harsh environments. Here, a comprehensive research progress and in‐depth understanding of the critical factors leading to the poor low‐temperature performance of LIBs is provided; the distinctive challenges on the anodes, electrolytes, cathodes, and electrolyte–electrodes interphases are sorted out, with a special focus on Li‐ion transport mechanism therein. Finally, promising strategies and solutions for improving low‐temperature performance are highlighted to maximize the working‐temperature range of the next‐generation high‐energy Li‐ion/metal batteries. Abstract : A timely and critical review on fundamental mechanisms, recent advances, and design strategies of electrolytes, electrodes, and battery structures for low‐temperature Li batteries is provided.